Is legal protection sufficient to ensure plant conservation? The Italian Red List of policy species as a case study. Issue 3 (28th April 2015) - Rossi, Graziano; Orsenigo, Simone; Montagnani, Chiara; Fenu, Giuseppe; Gargano, Domenico; Peruzzi, Lorenzo; Wagensommer, Robert P.; Foggi, Bruno; Bacchetta, Gianluigi; Domina, Gianniantonio; Conti, Fabio; Bartolucci, Fabrizio; et al.
Abstract: The conservation of species listed in the Bern Convention and European Directive 1992/43/EEC (so-called policy species) is mandatory for European Union (EU) countries. We assessed the conservation status of Italian policy species, based on the IUCN categories and criteria, to evaluate the effectiveness of existing protection measures at the national level. Among the 203 vascular plants, bryophytes and lichens evaluated, 41.9% are categorized as threatened, and one is already extinct, indicating that the protection measures for policy species are inadequate. Our results for the Italian policy species are consistent with those of an assessment at the EU level. Conservation priorities should be established at both the national and regional scales. An effective conservation strategy is needed, and in situ and ex situ actions focused on threatened species should be promoted.